Optimal Unemployment Insurance with Program Interactions - Zachary Parolin; Clemente Pignatti (Institute of Labor Economics (IZA), 2024)
We study the interaction between unemployment insurance (UI) and other social transfers exploiting state-level changes to UI generosity and data from the Survey of Income and Program Participation (1990-2013). We find that more generous UI leads to a reduction in the receipt of other public transfers. This results from a short-term decrease in the probability of receiving means-tested programs, like the Supplemental Nutrition Assistance Program, and a long-term reduction in the probability of receiving Social Security benefits. Accounting for these interactions, the optimal UI replacement rate may be 17 percentage points higher than the current rate in the US.
Keywords: J01; J08; J65; 330; unemployment insurance; social security; welfare analysis